GENETIC EVALUATION OF INDIGENOUS AND EXOTIC WHEAT GERMPLASM BASED ON YIELD RELATED ATTRIBUTES - AMMAR, A; Ghafoor, S; AKRAM, AUA; ASHRAF, W; AKHTAR, S; NAWAZ, MS; ZAGHUM, MJ; KHAN, MY; AAS, MA; SHAHEEN, A; KHALID, MN; KASHIF, M (Biological and Clinical Sciences Research Journal, 2022)
Wheat is highly self-pollinated crop and main staple food of the world. Yield is one of the main breeding objectives in the wheat crop. Plant breeders are focusing on the development of new lines with increased yield, resistant against biotic and abiotic factors and having more nutritional values. The goal of the current research was to identify acceptable crossings for further investigation by determining the type of gene action (genetic effects) and combining ability of parental genotypes for morphological features. This approach was used to evaluate three lines, namely Ujala-2016, Johar-2016, Galaxy-2013 and four testers’ viz. XJ22, XJ23, XJ24 and XJ25. Collected data were subjected to line × tester analysis. Among parents as lines genotype Johar-2016 found good general combiner for studied traits. While among testers XJ25 proved to be the best general combiner for studied traits. Similarly, cross combinations hybrid XJ25 × Galaxy-2013 performed best as specific combiner. It was noticed that SCA variance was greater than GCA variance for all factors studied in wheat except for grains/spike. The superior genotypes and crosses can be further tested in yield for development of improved wheat varieties.